Multimodal Depiction of Israelis and Palestinians on Gaza Conflict in Two Middle Eastern Press - Robiatul Adawiyah; Esti Junining; Sri Endah Tabiati (Unipdu Jombang, 2020)
AbstractThis study aims to examine how two Middle Eastern Press, Daily Sabah and Iran Daily in depicting Israeli and Palestinians on Gaza conflict. This study carries out Multimodal Critical Discourse Analysis to uncover ideology of media. In other words, it focuses not only on the linguistic features but also semiotic resources realized through images. It analyses clauses that contain Van Dijk’s ideological square discourse using transitivity by Halliday (2004) and images existed in the selected articles using representational function of image by Kress & van Leeuwen (2006). The results show that both media represented Palestinians as Self-group whereas Israelis as Other-group. They portrayed the Self as the victims and right fighter in contrast to the Other as the agent of offensiveness.Keywords: Gaza conflict, multimodal critical discourse analysis, representational function of image, transitivity AbstrakPenelitian ini bertujuan untuk menjelaskan bagaimana dua koran Timur Tengah, Daily Sabah dan Iran Daily, dalam merepresentasikan pihak Israel dan Palestina dalam konflik Gaza. Penelitian ini menerapkan analisis wacana kritis multimodal untuk mengungkap ideologi dari dua koran tersebut. Dengan kata lain, penelitian ini tidak hanya fokus pada aspek linguistik saja namun juga pada aspek semiotik lainnya yang direalisasikan dalam bentuk foto. Data dalam penelitian ini meliputi 1) klausa-klausa yang mengandung strategi wacana ‘ideological square’ yang akan dianalisis menggunakan transitivitas oleh Halliday (2004), dan 2) semua foto yang ada di artikel yang dianalisis menggunakan fungsi representasi gambar oleh Kress & van Leeuwen (2006). Hasil dari penelitian ini menunjukkan bahwa kedua media tersebut merepresentasikan pihak Palestina sebagai self-group, pihak yang menjadi korban dan pembela hak, sedangkan pihak Israel sebagai other-group, pihak yang menjadi pelaku penyerangan.Kata kunci: analisis wacana kritis multimodal, konflik Gaza, fungsi representasi gambar transitivitas